2007
DOI: 10.1021/np0605586
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Diversity of Phthalides from the Apiaceae

Abstract: Phthalides, and their corresponding dihydro and tetrahydro analogues, are components of several genera of the plant family Apiaceae. These taxa have been reported as exhibiting a wide range of bioactivities against experimental models of several illnesses and physiological conditions, including microbial and viral infections, stroke, tuberculosis, and vasoconstriction. Many of these genera are purported to possess medicinal values, and of these several are considered to be traditional herbal medicines. This re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
145
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(157 citation statements)
references
References 130 publications
2
145
0
1
Order By: Relevance
“…However, it has been suggested that the presence of five membered lactone ring in phthalides is responsible for their bioactivity (Beck and Chou, 2007). The amino acid cysteine, and certain enzymes (containing mercapto groups) play an important role in growth and normal activity of bacteria and other microorganisms.…”
Section: Mode Of Action Of Phthalides On Biological Systemsmentioning
confidence: 99%
“…However, it has been suggested that the presence of five membered lactone ring in phthalides is responsible for their bioactivity (Beck and Chou, 2007). The amino acid cysteine, and certain enzymes (containing mercapto groups) play an important role in growth and normal activity of bacteria and other microorganisms.…”
Section: Mode Of Action Of Phthalides On Biological Systemsmentioning
confidence: 99%
“…It is a well-known constituent of the aroma of dairy products and some fruits [15]. cis-3a,4,7,7a-Tetrahydro-1(3H)-isobenzofuranone is the precursor of the phthalide-derived lactones that are abundant in fruits in the family Apiaceae, which are characterized by a celery-like aroma [16]. 1-Phenylethyl acetate is a well-known flavoring used in many countries as a food additive.…”
Section: Introductionmentioning
confidence: 99%
“…Such lactones, comprising a large group of phthalide derivatives, are isolated from plants of the family Apiaceae Lindl. They possess very attractive biological activities [40][41][42]. We are especially interested in the biosynthesis of enantiomerically-pure bicyclic lactones with selective growth inhibitory activities towards filamentous fungi of Aspergillus, Penicillium and Fusarium genera.…”
Section: Introductionmentioning
confidence: 99%